2015
DOI: 10.1542/peds.2015-2677
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Barriers to Pediatric Care in Limited-Resource Settings: A Simulation Study

Abstract: OBJECTIVES: Eighty percent of the 10 million annual deaths in children aged ,5 years in developing countries are estimated to be avoidable, with improvements in education for pediatric emergency management being a key factor. Education must take into account cultural considerations to be effective. Study objectives were: (1) to use simulation to identify factors posing barriers to patient care in limited resource settings (LRS); and (2) to understand how simulations in LRS can affect communication and decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Additional recommendations related to increasing group participation and including doctors in both simulations and debriefs. A previous study in Bihar similarly suggested that inclusion of doctors in simulation training leads to improved communication and reduced hierarchy in PHCs [43]. This is consistent with previous studies in Rwanda and Kenya that highlighted the importance of teamwork [44] and leadership buy-in, respectively [45].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additional recommendations related to increasing group participation and including doctors in both simulations and debriefs. A previous study in Bihar similarly suggested that inclusion of doctors in simulation training leads to improved communication and reduced hierarchy in PHCs [43]. This is consistent with previous studies in Rwanda and Kenya that highlighted the importance of teamwork [44] and leadership buy-in, respectively [45].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with previous studies that have recommended adaptation of debriefs to fit the environment and skill level of trainees [12]. Acceptability of this flexible approach to debriefing is critical, as government-run PHCs in India often face severe human resource shortages and, as a result, clinical duties are routinely prioritized over training [24,43]. Additional recommendations related to increasing group participation and including doctors in both simulations and debriefs.…”
Section: Discussionsupporting
confidence: 83%
“…Another challenge to teaching these courses is the task of simulating the core critical care concepts of teamwork and collaborative learning in settings where these are not commonly practiced ( 49 ). In some cases, these difficulties may be due to cultural and hierarchical attitudes, but, nevertheless, could hinder training in optimal resuscitation and ongoing care.…”
Section: Standardized Course: Evidence and Challengesmentioning
confidence: 99%
“…These types of general guideline-driven interventions with several components have been shown to improve outcomes in emergency care [12,22], but the evidence (especially from clinical trials) for each component of the intervention is lacking. Training staff as teams can also help bring about positive changes in clinical environments and improve communication [23]. But, despite evidence for improved outcomes with protocols and algorithms for care, the study by Nyirasafari et al highlights that their PICU was unable to adopt them, possibly because the unit was new or because of the patient burden combined with limited staff and resources [10].…”
mentioning
confidence: 99%